APLIKASI INFORMASI TABLIGH AKBAR DI MAKASSAR BERBASIS ANDROID MENGGUNAKAN METODE PROTOTIPE - Inggi Amalia Faisal; Syaiful Rahman; Hendra Surasa (KHARISMA Tech, 2020)
This study aims to design a large Android-based tabligh information application. Data collection is done through prototype evaluation using the System Usability Scale (SUS) method developed by researchers and involving 20 respondents. After the evaluation is conducted, respondents are asked to answer the questions raised on the questionnaire and the results are used as a basis for drawing conclusions. In this research, the writer makes an Android-based tabligh akbar information application system to facilitate users in getting great tabligh information in Makassar. The system consists of two major parts. The first part consists of the web server and MySQL database. The second part consists of the Android Application. The server side is used by the admin in processing data Tabligh akbar schedule and others. While the Android-based Tabligh akbar application is used by mobile smartphone users. The results of testing with the System Usability Scale (SUS) method produces an average score of 79 which shows that the system created gets a good rating from respondents.